SECI-SYS: secretariat database management system / Nor Syamimi Iliani Che Hassan ...[et al.] - Che Hassan, Nor Syamimi Iliani; Mohammad Nor, Nor Hairunnisa; Awang, Nur Amalina; Raja Yacob, Raja Nur Hidayah (Universiti Teknologi MARA Kelantan, 2020)
SECI-SYS is a system software developed as a platform to store, retrieve, and update data regarding information management. Secretariat, in this regard acts as the people responsible for maintaining effective records and file administration. In conjunction with 2nd Kelantan International Learning and Innovation Exhibition 2019 (KILIEx 2019), SECISYS is established to ensure the management of data is consistently organized and remained to be easily accessible by the end users. SECI-SYS is governed by the information processing cycle which consists of four major stages; input, processing, storage and output. In brief, the procedures include data entry (input stage) followed by data coding and updating (processing stage), data keeping (storage stage) and finally producing desired data for respective users (output stage). Due to the varying needs from multiple angles, SECI-SYS plays a pivotal role as the core data feeder to enable the committees to access the information. In the absence of SECI-SYS, missing of files, overlapping of information, and iscommunication as a whole, shall be expected to occur. Consequently, database management system for KILIEx 2019 will be dysfunctional thus, disrupt the flow of the event. With this SECI-SYS, the anagement of database will be made convenient due to its multiple access, user-friendly, cloud storage function and zero charge for its development. SECI-SYS allows room for additional features to be included in order to maximize the functions for advanced users such as the merging data for managing pharma ommercialization due to its marketabilit